Reconstruction of the Meaning of Learning Motivation of Students from Low Socioeconomic Backgrounds in Continuing Higher Education - Intan Purnamasari (Fitrah, 2026)
Students from low socioeconomic backgrounds often face various limitations in accessing education, such as financial constraints, learning facilities, and information about higher education opportunities. These conditions have the potential to influence their learning motivation and decisions to continue their education to a higher level. This study aims to analyze the meaning of learning motivation for low socioeconomic students in their efforts to continue their education to a higher level. The study used a library research method by reviewing various scientific literature such as books, articles, and journals that align with the research theme. Data were analyzed using content analysis techniques to identify concepts, patterns, and findings related to learning motivation and students' socioeconomic conditions. The results of the study indicate that learning motivation plays a significant role in encouraging low socioeconomic students to continue their education. This motivation is interpreted as a drive to improve living conditions, achieve goals, make their families proud, and achieve a better future. In addition to intrinsic motivation, support from parents, teachers, the school environment, and access to educational information also contribute to strengthening students' enthusiasm in overcoming various economic limitations. Therefore, inclusive educational support, adequate access to information, and educational assistance programs are needed to increase students' opportunities to continue their higher education.